The Politics and Polemics of Culture in Ireland, 1800–2010 by Pat Cooke (2022), Routledge - Vaughan, Connell (Irish Journal of Arts Management and Cultural Policy, 2022)
Cooke’s book surveys the history of cultural policy and discourse from the Act of Union to the Financial Crash of 2008. It demonstrates the different ways the role of culture has been conceived by the state with an eye for the ideological ironies when theory is put into practice. Particular focus is devoted to the postcolonial nature of these ironies. The author does not find cultural policy to be a result of deliberative and democratic processes. Rather it is largely ad-hoc, idiosyncratic, and personality-driven.